Novel RNAseq-Informed Cell-type Markers and Their Regulation Alter Paradigms of Dictyostelium Developmental Control - Forbes, Gillian; Chen, Zhi-Hui; Kin, Koryu; Schaap, Pauline (Frontiers in Cell and Developmental Biology, 2022)
Cell differentiation is traditionally monitored with a few marker genes, which may bias results. To understand the evolution and regulation of the spore, stalk, cup and basal disc cells in Dictyostelia, we previously performed RNAseq on purified cell-types of taxon-group representative dictyostelids. Using promoter-lacZ constructs in D. discoideum, we here investigate the spatio-temporal expression pattern of 29 cell-type specific genes. Genes selected for spore- or cup- specificity in RNAseq were validated as such by lacZ expression, but genes selected for stalk-specificity showed variable additional expression in basal disc, early cup or prestalk populations. We measured responses of 25 genes to 15 single or combined regimes of induction by stimuli known to regulate cell differentiation. The outcomes of these experiments were subjected to hierarchical clustering to identify whether common modes of regulation were correlated with specific expression patterns. The analysis identified a cluster combining the spore and cup genes, which shared upregulation by 8-bromo cyclic AMP and down-regulation by Differentiation Inducing Factor 1 (DIF-1). Most stalk-expressed genes combined into a single cluster and shared strong upregulation by cyclic di-guanylate (c-di-GMP), and synergistic upregulation by combined DIF-1 and c-di-GMP. There was no clustering of genes expressed in other soma besides the stalk, but two genes that were only expressed in the stalk did not respond to any stimuli. In contrast to current models, the study indicates the existence of a stem-cell like soma population in slugs, whose members only acquire ultimate cell fate after progressing to their terminal location during fruiting body morphogenesis